Many Shades of bhakti: A Devoted Second Wife and Self-decapitated Bhairava - Ewa Dębicka-Borek (Ksiegarnia Akademicka Publishing, 2019)
Many Shades of bhakti: A Devoted Second Wife and Self-decapitated Bhairava